Pengaruh Kepemimpinan, Lingkungan Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan PT. SIG - Agus Sukma Cahyo Adi; Tjiptogoro Dinarjo Soehari (Manajerial, 2015)
The purpose of this research was to analyze the effect of leadership, work environment, and job satisfaction on employee performance at PT SIG. The method used in this research is an survey methode on 112 respondent. Primary data collected by questionnaires. The research was conducted by analysis correlation and regression. Hypothesis test result showed that there is a positive and significant influence of the leadership, work environment and job satisfaction on employee performance.